Challenges of Indonesian elementary school mathematics teachers in integrating critical thinking into the classroom - Trisnani, Novy; Retnawati, Heri; Wuryandani, Wuri (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
This study addresses the pressing need to develop critical thinking skills in young learners, which is essential for 21st-century education. Focusing on Indonesian elementary school mathematics teachers, this research provides new insights into the specific challenges they encounter a context that has been underexplored in the existing literature. The primary objective of this study is to identify the barriers these teachers face when integrating critical thinking skills into their mathematics instruction. Utilizing a qualitative approach, the research employs open-ended online surveys, allowing participants to respond to their own words rather than selecting from predefined options. Convenience sampling was used to recruit participants, resulting in a sample of 114 teachers from ten provinces across Indonesia. Data from the surveys were analyzed thematically and inductively using constant comparative methods. The analysis identified that the major obstacles to integrating critical thinking skills into mathematics education were limitations related to time and resources (accounting for 71.34% of identified barriers), along with deficiencies in pedagogical knowledge, confidence, and skepticism about the expected outcomes. The findings of this study offer valuable insights into the considerations necessary for successfully incorporating critical thinking skills into elementary mathematics instruction and highlight the potential for enhancing teacher effectiveness in this area.